Kemampuan Manajerial Kepala Sekolah Dalam Meningkatkan Kinerja Guru Untuk Menciptakan Sekolah Yang Bermutu: Penelitian di SDIT Sabilul Huda dan SDIT Sains al-Farabi - Asep Kurniawan (LP2M IAIN Syekh Nurjati Cirebon, 2011)
The topic of this research is “Managerial Skill of the Principals to Increase Teacher›s Performance in Promoting Excellence School (Research in SDIT Sabilul Huda and SDIT Sains al-Farabi)”. Based on the fact that management skill of the principals contributed to teachers performance, and in any way related in increasing the quality of teaching and learning in the school.The purpose of this research is to elaborate the role of the principals in implementing management functions: planning, organizing, actuating, controlling and evaluating of school resources; in order to promote better teaching and learning in the class through teacher›s performance. Research used descriptive qualitative approach, while data collected by interview, observation, and documentation study, focused on the principals, teachers, and school committee.Characteristic of the sample is SDIT Sabilul Huda at the educational area and SDIT Sains al-Farabi at non educational area. Research concluded: (1) the principals in general have implemented school based management (SBM) through implementation principles of management functions: planning, organizing, controlling, and evaluating in increasing the goal of teaching and learning in the school. (2) Teachers performance is really good and produced better teaching process. (3) The school committee always encourages and support the school beside to supervise and to facilitate the development of teaching quality. (4) The difference of community participation due to limited of resources and prosperity. (5) Principals created to promote students’ achievement through collaboration with the parent and school committee. Research recommended (1) SDIT Sabilul Huda school must promote to be benchmarking school for academic achievement and education of religious values. (2) SDIT Sains al-Farabi should promote to be excellence school in the sciences faulty world view cannot be separated with religious values. (4) Education office should facilitate financial and school facilities in order to increase better teaching and learning process. (5) Supervisors should be proactive in carrying out their duties. (6) Further research is needed to complete these findings.